Regional changes in thalamic shape and volume are related to cognitive performance in multiple sclerosis. (January 2021) - Bisecco, Alvino; Capuano, Rocco; Caiazzo, Giuseppina; d'Ambrosio, Alessandro; Docimo, Renato; Cirillo, Mario; Russo, Antonio; Altieri, Manuela; Bonavita, Simona; Rocca, Maria A; Filippi, Massimo; Tedeschi, Gioacchino; et al.
Background: The relationship between cognitive performance and regional thalamic atrophy in multiple sclerosis (MS) has been investigated in recent studies. Objective and methods: To further assess this relationship, 118 relapsing-remitting MS patients and 52 healthy controls underwent a neuropsychological assessment and a 3T-MRI (3-Tesla magnetic resonance imaging). Cognitive performances were correlated with thalamic shape changes by using Vertex Analysis. Results: Information processing speed performance correlated with atrophy of frontal/motor-connected thalamic sub-regions. Inhibitory control performance correlated with atrophy of all thalamic sub-regions. Global cognitive status correlated with atrophy of frontal/temporal-connected sub-regions. Conclusions: These findings support the hypothesis that, within the thalamus, the damage of the anterior regions is most relevant for cognitive dysfunction.